PERSEPSI MASYARAKAT TERHADAP PEMANFAATAN TANAMAN AREN (Arenga pinnata Merr) DI DESA SEKABUK KECAMATAN SADANIANG KABAUPATEN MEMPAWAH - Paulus, Paulus; Zainal, Sofyan; Oramahi, H A (Universitas Tanjungpura, 2020)
This research is aimed at describing people’s perceptions of utilization sugar palm plants in the village of Sekabuk Sadaniang sub-district, as well as analyzing the relationship of each of the factor of age, knowledge, and income with people’s perceptions of the utilization of palm plants in the village of Sekabuk Saadaniang sub-district. This research uses direct interview technique method with questionnaire tool, determination of respondents carried out by purposive sampling based on slovin formula amounting to 83 respondents, the criteria of respondents in the research are people who live in the village of Sekabuk, people who know about the use of palm trees, at least 15 years old (already married), physically and mentally healthy. Data analysis consisted of community perceptions of the use of palm trees and the relationship between age, knowledge, and income with community perceptions of the use of palm trees in Sekabuk village. Based on the results of data and calculations of the three variables, forage and knowledge categories there is no relationship with community perceptions, while the income category is related to people’s perceptions. The results of the study showed that community perceptions of the utilization of sugar palm plants tended to be positive namely 77 respondents (92,77%), neutral 6 respondents (7,23%), and negative 0 respondents (0,00%). Characteristics of Sekabuk village respondents based on age levels dominated by young and adult levels each of 30 respondents (36,14%). Characteristics of respondents based on the level of knowledge dominated by people with a high level of knowledge of 81 respondents (97,60%), and for the characteristics of respondents based on the level of income dominated with a moderate income level of 65 respondents (79,52%).Keywords: Community perception, Utilization Of Palm Sugar Plants